The Growth Return of Infrastructure in Latin America - Sergi Lanau (International Monetary Fund, 2017)
This paper examines the effects of improvements in infrastrucutre on sectoral growth and firm-level investment, focusing on six Latin American countries. Exploiting the heterogeneity in the quality of infrastructure across countries and the intrinsic variation in the dependence of sectors on infrastructure, I find that better infrastructure raises growth and investment. Improved infrastructure could yield large economic benefits. For example, if the quality of infrastructure in Colombia increased to the sample median (Czech Republic), GDP growth would increase by about 0.1 percentage points.